2016
DOI: 10.1002/ange.201608780
|View full text |Cite
|
Sign up to set email alerts
|

H2S Sensors: Fumarate‐Based fcu‐MOF Thin Film Grown on a Capacitive Interdigitated Electrode

Abstract: Herein we report the fabrication of an advanced sensor for the detection of hydrogen sulfide (H 2 S) at room temperature,u sing thin films of rare-earth metal (RE)-based metal-organic framework (MOF) with underlying fcu topology.T his unique MOF-based sensor is made via the in situ growth of fumarate-based fcu-MOF (fum-fcu-MOF) thin film on ac apacitive interdigitated electrode.T he sensor showed ar emarkable detection sensitivity for H 2 Sa tc oncentrations down to 100 ppb,w ith the lower detection limit arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…AlFFIVE-1-Ni exhibits relatively higher pore volume due to the presence of [AlF5] 2inorganic pillar (after activation) and provide higher capture amount for hydrocarbons than NbOFFIVE-1-Ni. These subtle differences in the intrinsic structural features demonstrated very interesting properties for separation and sensing of CO2, H2O, H2S and SO2 [14][15][16][17][18][25][26]. Most importantly, NbOFFIVE-1-Ni was found to adsorb C3H6 and exclude fully C3H8 while very poor C3H6/C3H8 selectivity was observed for AlFFIVE-1-Ni, in addition both NbOFFIVE-1-Ni and AlFFIVE-1-Ni exhibit extremely high hydrolytic stability and can capture CO2 and water concurrently with high selectivity [17] but with different performances at different operation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…AlFFIVE-1-Ni exhibits relatively higher pore volume due to the presence of [AlF5] 2inorganic pillar (after activation) and provide higher capture amount for hydrocarbons than NbOFFIVE-1-Ni. These subtle differences in the intrinsic structural features demonstrated very interesting properties for separation and sensing of CO2, H2O, H2S and SO2 [14][15][16][17][18][25][26]. Most importantly, NbOFFIVE-1-Ni was found to adsorb C3H6 and exclude fully C3H8 while very poor C3H6/C3H8 selectivity was observed for AlFFIVE-1-Ni, in addition both NbOFFIVE-1-Ni and AlFFIVE-1-Ni exhibit extremely high hydrolytic stability and can capture CO2 and water concurrently with high selectivity [17] but with different performances at different operation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Metal organic frameworks (MOFs) offer highly selective and sensitive detection of H 2 S because of possessing chemical stability, custom tuning of porosity and functionalities, and various pre- or post-synthetic modifications to the structural framework [ 173 ]. Guo et al [ 174 ] synthesized a MOF material named as Zr(TBAPy) 5 (TCPP) using a solvothermal method, where Zr is the metal center, and 1,3,6,8-tetra(4-carboxylphenyl) pyrene (TBAPy) and tetrakis(4-carboxyphenyl) porphyrin (TCPP) act as double linkers.…”
Section: Recent Advances In H 2 S Gas Detectionmentioning
confidence: 99%
“…Images reproduced with permission from reference [22], copyright 2016 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Figurementioning
confidence: 99%
“…Later in 2016, Yassine et al reported a capacitive sensor fabricated by growing thin films of a fumarate—based yttrium MOF, in which hexanuclear Y clusters are connected by fumarate ligands in a UiO-66-type structure, onto IDEs that had been functionalized with a self-assembled monolayer of 11-mercaptoundecanol [ 22 ]. These capacitive sensors displayed extraordinary sensitivity to H 2 S vapors (≤100 ppb) at room temperature, and high selectivity for H 2 S over other gases such as NO 2 , CH 4 , H 2 , and toluene ( Figure 2 ).…”
Section: Mof-based Gas Sensorsmentioning
confidence: 99%
See 1 more Smart Citation